2019
DOI: 10.1016/j.bandl.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive correlates of category ambiguous verb processing: The single versus dual lexical entry hypotheses

Abstract: Word-class ambiguous words engender greater processing time and fMRI (BOLD signal) activation than unambiguous ones. Theoretical accounts of this phenomenon suggest that words with multiple meanings (1) are associated with multiple lexical entries and thus require greater selection demands, or (2) undergo computationally expensive grammatical processes that convert words from one word-class to another. Using an fMRI grammaticality judgment task, we tested these accounts by examining word-class ambiguous polyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…Full priming in the inflected condition arises due to repeated access to the same representational structure comprising the basic entry and the verb-specific subentry that had both been preactivated by the prime. Neuro-imaging data has recently been reported that supports such a view by indicating that polysemic verbs may share a core representation with their noun counterparts (Lukic et al, 2019). Further research is necessary to identify which version of the Hypothesis 2a grasps the representation of nonfinites best.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Full priming in the inflected condition arises due to repeated access to the same representational structure comprising the basic entry and the verb-specific subentry that had both been preactivated by the prime. Neuro-imaging data has recently been reported that supports such a view by indicating that polysemic verbs may share a core representation with their noun counterparts (Lukic et al, 2019). Further research is necessary to identify which version of the Hypothesis 2a grasps the representation of nonfinites best.…”
Section: Discussionmentioning
confidence: 97%
“…data has recently been reported that supports such a view by indicating that polysemic verbs may share a core representation with their noun counterparts (Lukic et al, 2019). Further research is necessary to identify which version of the Hypothesis 2a grasps the representation of nonfinites best.…”
Section: Supplementary Materialsmentioning
confidence: 93%
“…For the critical ambiguous words, both response options (the two meanings of the noun-verb homonyms) are available and compete for selection, leading to increased use of computational resources (see Beretta et al, 2005 ; Eddington and Tokowicz, 2015 ). On the other hand, the observed ambiguity effect may also reflect the cost of deriving a more complex structure, given that the ambiguous word would be compatible with the base and derived structure (unlike “paper” which is ambiguous just in meaning), and thus might incur additional processing costs ( Lukic et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another novelty in our work is that we use a multivariate brain encoding approach, in combination with computational models. Previous studies of the interplay between semantic composition and polysemic variation in the interpretation of lexical items in cognitive neuroscience (Klepousniotou, Pike, Steinhauer, & Gracco, 2012; Klepousniotou, Gracco, & Pike, 2014; Lukic, Meltzer‐Asscher, Higgins, Parrish, & Thompson, 2019; MacGregor, Bouwsema, & Klepousniotou, 2015; Mollica et al., 2020; Pylkkänen, Llinás, & Murphy, 2006; Pylkkänen & McElree, 2007; Pylkkänen, 2020) have all used univariate methods (e.g., looking at differences in BOLD activation across conditions), whereas multivariate analyses afford higher sensitivity and, more importantly, a way to test competing accounts (Hebart & Baker, 2018; Naselaris & Kay, 2015).…”
Section: Introductionmentioning
confidence: 99%